Meat cutting and processing for food service - British Columbia Cook Articulation Committee; BC Open Textbook Project; BCcampus (BCcampus, BC Open Textbook Project, 2014)
"This book is intended to give students a basic understanding of the various types of meat and poultry used in the food service industry, and of how the terminology used by retail, wholesale, and food service customers varies. Meat cutting for restaurants and hotels differs slightly from meat cutting for retail. Restaurants and hotels sometimes use names of cuts on menus that are common in the kitchen vernacular or in other jurisdictions like Europe or the United States, while retail meat cutters are bound by Canadian regulations regarding labelling and marketing of meat products to consumers for retail. Meat Cutting and Processing for Food Service is one of a series of Culinary Arts books developed to support the training of students and apprentices in British Columbia's food service and hospitality industry. Although created with the Professional Cook and Baker programs in mind, these have been designed as a modular series, and therefore can be used to support a wide variety of programs that offer training in food service skills."--BC Campus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online resource; title from pdf title page (viewed on January 7, 2016).
Keywords: Meat cutting -- Textbooks; Electronic books